Bodies, masculinities and sports. The covers of “El Gráfico” magazine, Argentina 1920-1930 - Scharagrodsky, Pablo (Universidad del Pacífico, 2021)
The following work analyzes the ways in which one of the most important sports magazines in Argentina, “El Gráfico”, in the 1920s and 1930s presented and (re) presented men in the wide and diverse universe of physical and sports culture. To investigate the different senses on masculinity, we focus our attention on the covers of the famous magazine. Based on a qualitative methodology that articulated the hermeneutic historical analysis, visual history and gender studies, the dominant male body model has been identified and condensed different meanings: strength, courage, skill, chivalry, tactical intelligence, 'Creole' mischief, antagonism, physical display; resistance, character, dynamism, sense of national belonging; and social recognition, nobility and status.